1979
DOI: 10.1159/000122944
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Ablation of the Suprachiasmatic Nucleus. Effects on the Development of the Pituitary-Gonadal Axis in the Female Rat

Abstract: Ablation of the suprachiasmatic nucleus (SCN) at 2 days of age, prior to the formation of the retinohypothalamic projection, produces a permanent state of constant vaginal estrus in the postpubertal female rat. Although such lesions do not alter the onset of puberty in sighted rats, they do compensate for the delay in vaginal opening induced by neonatal blinding. The ovaries of sighted and blinded SCN-lesion rats are small and polyfoUicular and the pituitaries of blinded SCN-lesion rats are abnormally large. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…28,59 Disruption of biological rhythms across the HPO axis: animal studies Several pioneer studies have shown that SCN ablation or lesions in rats result in irregular estrous cycles and the inhi bition of LH surge and of ovulation. 23,60,61 These results have been confirmed by recent studies of core clock gene mutants and mutant cell lines.…”
supporting
confidence: 64%
“…28,59 Disruption of biological rhythms across the HPO axis: animal studies Several pioneer studies have shown that SCN ablation or lesions in rats result in irregular estrous cycles and the inhi bition of LH surge and of ovulation. 23,60,61 These results have been confirmed by recent studies of core clock gene mutants and mutant cell lines.…”
supporting
confidence: 64%
“…The SCN oscillator function is robust and is moderately resistant to mechanical damage (19,20 (25,26). The biological activity of f3/A4 and homologous peptides has been observed in several experimental systems (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…The administration of barbiturates that prevent signaling within the SCN to rats prior to this event blocks the LH surge and ovulation and delays them for 24 h (3). Additionally, studies on SCN lesions in rats resulted in the absence of ovulation (46, 47). Combined, these studies provide evidence that a signal from the circadian system is crucial for successful ovulation.…”
Section: From Scn Through Hpg Axis To Sex Hormonesmentioning
confidence: 99%